Navigating a transforming landscape: the evolving role of pharmacovigilance physicians in drug development and implications for future challenges and training requirements - Hammad, Tarek A.; Afsar, Salman; Le-Louet, Herve; Kugener, Veronique F. (Frontiers in Drug Safety and Regulation, 2023)
Contrary to the famous quote from Voltaire, "The art of medicine consists in amusing the patient, while nature cures the disease", medicine has evolved since the seventeenth century into a multi-faceted scientific field facilitating healing and improving overall wellbeing. One rapidly evolving area within this field is drug safety, also known as pharmacovigilance (PV). PV identifies and evaluates potential risks throughout the life cycle of the drug, minimizing patient exposure to harmful effects and guiding appropriate risk mitigation and management strategies. Timely identification and mitigation of risks not only contribute to patient safety but also allows maximum therapeutic benefits while curtailing economic burden associated with adverse events. In the evolving landscape of drug safety, the role of the PV physicians has emerged as an integral component of drug development. This paper aims to explore the evolving nature of PV physicians’ roles in drug development, highlighting changing landscape in drug development and safety monitoring and attendant changes and advancements in responsibilities, scope, and training implications. To be well-rounded, PV physicians are encouraged to strive to undergo relevant training and education. This would enable them to leverage pertinent complementary fields of science by developing the proficiency to ask the right questions, acknowledge multidisciplinary perspectives, and interpret the overall evidence. While on-the-job training is valuable for gaining experience, building a future safety workforce necessitates more targeted efforts, especially considering that medical school curricula may not readily emphasize the development of skills required for successful PV physician roles. Therefore, academic centers, pharmaceutical companies, and regulatory agencies should increase collaboration to establish hands-on training opportunities through post-doctoral, internship, and fellowship programs, in order to meet the growing demand for well-trained PV physicians.